Série apontamentos: um periódico comprometido com a interação entre a linguagem fílmica e os seus aspectos pedagógicos - Lima, Marileide Santana (2009)
This research has the intention to presents Série Apontamentos , a periodical that suggests, by publication text, the interaction between filmic language and its pedagogical aspects. Special attention is given to the film as a tool to support teaching practice. This work is inserted in the research of the history and theory of teaching profession. For the purposes of this inquiry, were used the following methodologies: analysis of documents, periodicals, dissertations, and complement literature of the Série Apontamentos .